LEVERAGING EXCEL AS RESOURCE: BOOSTING THE FINANCIAL REPORTING PROFICIENCY OF SHARIAH ACCOUNTING - Trie Nadilla (Universitas Muhammadiyah Tangerang, 2025)
In higher education, studying theory alone is not enough, but also requires experience and developing skills needed in the world of work. So it is hoped that graduates will be able to compete in the world of work. Including in the world of the accounting profession. The accounting profession is closely tied to the business environment because they play a very active role in economic activities. The demand for computerized practical skills is something that is non-negotiable for the skills of graduated. one learning medium is to provide guidance and training on how to present computerized financial reports by utilizing the pivotable function of the Microsoft Excel accounting program. The results of the Forum Discussion Group (FGD) suggest that students majoring in sharia accounting are able to master accounting information applications, at least Excel software.Â The method used in this research is an experimental method. pre-experimen.t The experiment was carried out using a one group pretest-posttest design. The research results show differences in the capacity of sharia accounting students in making financial reports before and after studying Excel accounting. This means there is influence on increasing the capacity of sharia accounting students at the Faculty of Islamic Economics and Business.